Design and development of an optical sensor system to measure visibility of air - S., Nurulain; R. M., Ramli; H., Manap (Springer, 2020)
Visibility is a measure of the distance at which an object or light can be clearly recognized. Visibility for a medium depends on the visible light transmission (VLT). This paper describes the development of VLT measurement system to measure the visibility of air. In recent years, there are many types of devices that can measure VLT. But the existing method and technique have their own disadvantages such as gigantic set up, costly, only can be used in small area and fail to function at night. Therefore, this research will focus on how to measure the visibility by using an open path optical method. The experimental setup for VLT measurement in this research consists of a laser pointer as a light source and spectrometer as a detector. The amount of light that passes through a few series of known-VLT thin films is measured and the percentage values of the measured thin film are set as a measurement base. This new proposed technique is believed to cater the problem mentioned above as the experimental setup is simple, small in size and can measure visibility in any light condition.